Analysis of Demand and Competition for Indonesian Frozen Tilapia Fillet with Major Competitors in the International Market - Mutiara Ria Despita Maharani; Muhammad Ali Yafi; Musyafak Musyafak (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Frozen tilapia fillets are the only farmed fish among Indonesia's leading fishery export commodities. Fierce competition requires Indonesia to maintain its position. This study aims to analyze the demand for and competition with major competitor countries in the international market for Indonesian frozen tilapia fillets. This study employs the Almost Ideal Demand System (AIDS) and estimates it using the Seemingly Unrelated Regression (SUR) method. The data source is secondary data obtained from ITC Trade Map with HS code 030461 (Frozen fillets of tilapia